Green low-carbon high-performance sprayed concrete using active regenerated micro-powder, and preparation method and construction process of green low-carbon high-performance sprayed concrete

A green, low-carbon shotcrete formulation using active regenerated micropowder and tailored aggregates addresses the challenge of reducing cement dosage, enhancing early strength and durability, and improving construction efficiency.

CN119143440AActive Publication Date: 2024-12-17JIANGSU SOBUTE NEW MATERIALS CO LTD

Patent Information

Application Number
CN202411047903.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-07-31
Publication Date
2024-12-17
Estimated Expiration
2044-07-31

AI Technical Summary

Technical Problem

Existing shotcrete technologies face challenges in reducing cement dosage while maintaining early strength, durability, and environmental impact, leading to issues such as shrinkage cracking, high carbon emissions, and decreased construction efficiency.

Method used

A green, low-carbon shotcrete formulation using active regenerated micropowder, comprising cement, active regenerated micropowder, early-strength mineral admixtures, rubber powder, hydrophobic densifier, and specific aggregates, along with a controlled construction process, to enhance early strength, durability, and workability.

Benefits of technology

The solution effectively reduces cement consumption, lowers carbon emissions, improves early strength and durability, and enhances construction efficiency by using active regenerated micropowder and tailored aggregates, while maintaining mechanical strength and reducing rebound rates.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004974015020000031
    Figure BDA0004974015020000031
  • Figure BDA0004974015020000061
    Figure BDA0004974015020000061
  • Figure BDA0004974015020000121
    Figure BDA0004974015020000121
Patent Text Reader

Abstract

The invention relates to the field of sprayed concrete, in particular to green low-carbon high-performance sprayed concrete using active regenerated micro powder and a preparation method and a construction process of the green low-carbon high-performance sprayed concrete. The sprayed concrete is prepared from the following components in parts by weight: 300 to 350 parts of cement, 50 to 80 parts of active regenerated micro powder, 60 to 120 parts of early strength type mineral admixture, 20 to 40 parts of rubber powder, 10 to 20 parts of hydrophobic compacting agent, 700 to 800 parts of coarse aggregate and 800 to 900 parts of fine aggregate, the mixing amount of the water reducing agent is 0.8%-1.2% of the mass of the cementing material, and the mixing amount of the fluoride-free alkali-free accelerator is 6%-9% of the mass of the cementing material; wherein the active regenerated micro powder is composed of multi-component isomeric alcohol amine and regenerated micro powder, and the dosage of the multi-component isomeric alcohol amine is 0.1%-0.5% of the mass of the cementing material. The cement consumption of the sprayed concrete can be reduced, and the requirement for high performance of the sprayed concrete is met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of shotcrete, and more specifically, to a green, low-carbon, high-performance shotcrete using active regenerated micropowder, and a preparation method and construction process thereof. Background Art

[0002] Shotcrete is a concrete mixture of cementitious materials, aggregates, etc. mixed in a certain proportion, which is sprayed at high speed onto the surface of rocks or buildings under the action of compressed air or other power sources. It solidifies and hardens in a short time under the action of accelerators to produce a certain strength, forming a concrete structure with sealing and supporting functions. It has many advantages such as high construction efficiency, simple process and good economic benefits. It can restrain and control the deformation of surrounding rocks and maintain the integrity of tunnel structures during construction and operation. It has been widely used in many fields such as transportation engineering, water conservancy and hydropower, mine support, underground engineering, repair and plugging of leaks, etc. It is the core material to ensure the safe construction and rapid construction of underground space structures.

[0003] Taking the Sichuan-Tibet Railway as an example, during the construction of the tunnel, affected by complex geological conditions such as rock bursts, large deformation of soft rocks, seepage and high ground temperature, the setting and hardening performance, early strength and durability of the initial support shotcrete of the tunnel are increasingly required. In response to this, most tunnel projects generally adopt a high-mixture pure cement cementitious system to ensure that the shotcrete has a faster rapid setting effect and early strength development. The single cubic meter cement dosage in some mixes even exceeds 500kg / m3. Although such a high cement dosage can meet the initial support strength requirements, it will increase the risks of shrinkage cracking and durability degradation during the later service of the shotcrete; in addition, cement is a high-energy consumption and high-pollution building material. Relevant data show that 8% of carbon dioxide in the global carbon emission process comes from cement. Therefore, how to reduce the cement dosage of shotcrete while meeting the service requirements of tunnel projects is a problem that needs to be solved urgently.

[0004] Patent No. CN112047708B "A shotcrete and its construction method" does not use traditional cement and accelerators, but prepares a new shotcrete through modified magnesium phosphate cement, mineral admixtures, setting regulators and other components. Although the rebound rate, compressive strength and durability are significantly improved, the types of materials used are too complex and the cost is too high, making it difficult to promote and apply on a large scale. Patent No. CN109437706A "A shotcrete and its preparation method and application" reduces the amount of cement by adding limestone powder as a mineral admixture. Although it can improve the workability of concrete mixtures and save construction costs, when the amount of limestone powder replaced increases, it will inevitably affect the setting and hardening speed and early strength of the shotcrete, and it cannot play the role of timely sealing the rock mass and stabilizing the surrounding rock. Patent No. CN108046712B "A high-strength, low-rebound shotcrete and its construction process" replaces part of the cement with silica fume and zeolite powder, and adds a certain amount of steel fiber to increase the toughness of shotcrete. Although it finally obtains a high-strength shotcrete with low rebound rate, high early strength, and 28d or even C60 strength grade, the components of silica fume, zeolite powder and steel fiber may greatly increase the viscosity of the concrete mixture, resulting in a decrease in pumpability, and even blockage of pipes, reducing construction efficiency. Patent No. CN110627446B "An economical and environmentally friendly tunnel shotcrete and construction process" improves the workability of shotcrete by increasing the sand ratio and using stone chips to replace part of the natural river sand, reducing the rebound rate and construction cost, but the cement consumption is still high. CN114620981A "A shotcrete and its preparation method and application" proposes to replace part of the cement with recycled concrete powder and to use nano seed crystal early strength agent to improve the early strength, but the recycled concrete powder used is not activated and only plays a certain filling role, which will affect the strength development of the shotcrete; in addition, the sand ratio in Examples 1 and 2 provided by the invention is too low, which may affect the workability of the concrete mixture and increase the risk of cracking in the later period; the water-cement ratio in Example 3 is too high, and the 8h and 1d compressive strengths are actually difficult to achieve the test results, and the 28d compressive strength is low, which will also affect the long-term durability.

[0005] Therefore, there is an urgent need to develop a green, low-carbon, high-performance shotcrete that can simultaneously meet the requirements of energy saving and environmental protection, good workability, low rebound rate, rapid early strength development, no shrinkage in later strength, and high durability, so as to ensure the high-quality construction of major national tunnel projects. It is of great significance to improving environmental quality, promoting the realization of the "dual carbon" strategy and the comprehensive green transformation of economic and social development. Summary of the invention

[0006] The present application provides a green, low-carbon, high-performance shotcrete using active regenerated micropowder and a preparation method and construction process thereof, aiming to reduce the cement consumption of shotcrete and meet the demand for high performance of shotcrete.

[0007] In the first aspect, the present application provides a green, low-carbon, high-performance shotcrete using active regenerated micropowder, which adopts the following technical solution:

[0008] A green, low-carbon, high-performance shotcrete using active regenerated micropowder, wherein the raw materials include the following components by weight: 300-350 parts of cement, 50-80 parts of active regenerated micropowder, 60-120 parts of early-strength mineral admixture, 20-40 parts of rubber powder, 10-20 parts of hydrophobic densifier, 700-800 parts of coarse aggregate, 800-900 parts of fine aggregate; a water reducer in an amount of 0.8% to 1.2% of the mass of the cementitious material, and a fluorine-free and alkali-free quick-setting agent in an amount of 6% to 9% of the mass of the cementitious material;

[0009] The active regenerated micropowder is composed of polyisomeric alcohol amine and regenerated micropowder, and the amount of the polyisomeric alcohol amine is 0.1% to 0.5% of the mass of the gelling material; the structural formula of the polyisomeric alcohol amine is as follows (Formula 1):

[0010]

[0011] Wherein, m=1 or 2, s=0, 1, 2, 3 or 4;

[0012] The early strength mineral admixture is a mixture of at least one of fly ash, slag powder, limestone powder and at least one of silica ash, zeolite powder, metakaolin, steel slag powder, phosphorus slag powder and an early strength agent, and the weight ratio of the three is (30-60): (30-40): (10-20) respectively.

[0013] Furthermore, the regenerated micro powder needs to meet the requirements of fineness (45 μm square hole sieve residue) ≤ 45%, particle size ≤ 75 μm, water requirement ratio ≤ 115%, and activity index ≥ 60%.

[0014] Furthermore, the fly ash is Class F Grade I fly ash, the slag powder is S105 grade slag powder, and the limestone powder has a 28d activity index of ≥70%. Further, the silica ash has a 28d activity index of ≥100%, the zeolite powder is Grade I zeolite powder, the steel slag powder is Grade I steel slag powder, the phosphorus slag powder is Grade L95 phosphorus slag powder, and the metakaolin is ultrafine kaolin calcined at 600°C to 900°C to form a high-activity powder particle with a particle size of about 1250 meshes. Further, the early strength agent is any one of sodium sulfate, calcium sulfate, magnesium sulfate, sodium thiosulfate, sodium thiocyanate, calcium nitrate, calcium nitrite, and sodium nitrate.

[0015] Furthermore, the rubber powder is waste tire rubber powder that has been surface treated, and the surface treatment includes any one of a water washing method, a pre-coating gelling material method, and a chemical solution immersion method.

[0016] Furthermore, the hydrophobic compacting agent is a silicone waterproofing agent or an emulsion waterproofing agent. Still further, the hydrophobic compacting agent is Type concrete anti-seepage hydrophobic compound pore plugs.

[0017] Furthermore, the coarse aggregate is natural crushed stone with continuous grading of 5 to 10 mm or crushed stone processed by crushing tunnel slag.

[0018] Furthermore, the fine aggregate is any one of natural river sand, machine-made sand or a mixture of natural river sand and machine-made sand, and the fineness modulus is 2.5 to 3.2.

[0019] Furthermore, the water reducer is a mixture of a polycarboxylate water reducer and a slump retaining agent, and the polycarboxylate water reducer is at least one of a carboxylate water reducer, a sulfonate water reducer, and a phosphonate water reducer.

[0020] Furthermore, the polycarboxylate water reducer is a mixture of a sulfonate water reducer and a phosphonate water reducer, and the mass ratio of the sulfonate water reducer to the phosphonate water reducer is 1:(1.5-3), and the phosphonate water reducer is a phosphonate water reducer with an acid-ether ratio of 2.0-2.5 and a molecular weight of 15,000-20,000.

[0021] In the second aspect, the present application provides a method for preparing green, low-carbon, high-performance shotcrete using active regenerated micropowder, which adopts the following technical solution:

[0022] A method for preparing green, low-carbon, high-performance shotcrete using active regenerated micropowder comprises the following steps:

[0023] S1. Dry mix cement, active regeneration powder, early strength mineral admixture, rubber powder, coarse aggregate and fine aggregate;

[0024] S2. Add water, water reducing agent and hydrophobic densifier in sequence and mix well to obtain a concrete mixture.

[0025] In the third aspect, the present application provides a construction process of green, low-carbon, high-performance shotcrete using active regenerated micropowder, which adopts the following technical solution:

[0026] A construction process for green, low-carbon, high-performance shotcrete using active regenerated micropowder, a construction project, wherein the concrete spraying distance is controlled at 0.8-1.2 m, the spraying angle is controlled at 80°-90°, the spraying wind pressure is controlled at 0.8-0.9 MPa, and the single-layer spraying thickness is not greater than 5 cm.

[0027] In summary, this application has the following beneficial effects:

[0028] 1. Firstly, this application replaces part of the cement by active regenerated micro powder and early strength mineral admixture, which can not only effectively reduce the amount of cement and reduce carbon emissions, but also has no adverse effect on the early strength of shotcrete.

[0029] For the active regenerated micropowder of the present application, unlike the traditional physical activation and thermal activation, the regenerated micropowder and the specific activator are directly mixed as the active regenerated micropowder, which can not only greatly reduce the energy consumption, but also is beneficial to the later strength and durability of the shotcrete. In addition, it is beneficial to control the rebound rate of the concrete and is suitable for the construction of shotcrete.

[0030] The use of early-strength mineral admixtures can make up for the early strength loss caused by the reduction in cement dosage. Moreover, when combined with active regenerated micropowder and cement, it can give full play to the complementary effect between powder material particles, form a good particle matching relationship, increase the density of shotcrete, and improve workability, mechanical strength and durability.

[0031] 2. The addition of rubber powder to shotcrete in this application can reduce the pollution of waste tires to the environment, and it is also a good way to modify shotcrete. The addition of an appropriate amount of rubber powder can improve the brittleness and toughness of shotcrete to a certain extent, and reduce the risk of cracking caused by stress concentration; not only that, because rubber powder is a hydrophobic material, bubbles are easily adsorbed on its surface, which is equivalent to a solid air-entraining agent that can be evenly and stably distributed in the shotcrete, thereby alleviating the hydrostatic pressure formed during the frost heave process and improving the frost resistance of the shotcrete. The present application also performs surface pretreatment on the rubber powder, which is beneficial to enhancing the interfacial bonding performance between the rubber powder and the cement matrix, thereby reducing the impact on the mechanical properties of the shotcrete.

[0032] 3. Since the sprayed concrete of this application is a special concrete, it is subject to the special spraying process and the early accelerated hydration effect of the accelerator. The overall structural density of the sprayed concrete is not as good as that of the cast concrete, and it is more susceptible to penetration by corrosive media such as sulfates and chlorides in the environment. In this application, by adding a hydrophobic densifier, the water absorption and permeability of the sprayed concrete can be further reduced, its durability in complex environments can be enhanced, and its service life can be extended.

[0033] 4. This application prefers to utilize tunnel slag to prepare coarse and fine aggregates, reduce the exploitation of natural river sand and gravel, and achieve green and low-carbon shotcrete together with recycled micro powder, mineral admixtures, and rubber powder.

[0034] 5. Since there is a certain amount of stone powder in the coarse and fine aggregates prepared from recycled micropowder and tunnel slag, they will have an adsorption effect on the water reducer, affecting the workability of the concrete mixture, which is very unfavorable for the construction of shotcrete. Therefore, the water reducer in this application is preferably a mixture of sulfonates and phosphonates, among which phosphonates have the best adaptability to recycled micropowder and stone powder, and will not significantly change the fluidity, yield stress and adsorption of the slurry, so it can play a good role in regulating the rheology of shotcrete.

[0035] 6. The preferred fluorine-free and alkali-free quick-setting agent in this application has a synergistic effect of early strength with the early strength mineral admixture, which can significantly improve the early strength development rate of shotcrete, while having no adverse effect on the later strength and durability. DETAILED DESCRIPTION

[0036] The present application is further described in detail below in conjunction with embodiments.

[0037] In the examples of this application, unless otherwise specified, all materials can be obtained from commercial sources. The specific details of the relevant materials are as follows:

[0038] The cement used is Nanjing Conch brand P·O42.5 ordinary Portland cement.

[0039] The rubber powder was 120 mesh rubber powder produced by Shaoyang Black Gem Rubber Technology Co., Ltd. It was soaked in 4% NaOH solution for 24 hours and dried before use.

[0040] The hydrophobic compacting agent is produced by Jiangsu Subote New Materials Co., Ltd. It is an anti-seepage and hydrophobic compound pore plug for concrete and is a light yellow transparent liquid.

[0041] Liquid alkali-free accelerating setting agent is produced by Jiangsu Subote New Materials Co., Ltd. Early-strength fluorine-free and alkali-free accelerator, fluoride ion content 0.01%, initial setting time of net paste 2min30s, final setting time of net paste 5min15s, mortar 6h compressive strength 2.2MPa, mortar 1d compressive strength 14.5MPa.

[0042] The coarse aggregate is 5-10mm continuously graded crushed stone processed by tunnel slag crushing, with a needle and flake particle content of 2.5%, a mud content of 0.2% and a mud block content of 0.1%.

[0043] The fine aggregate is machine-made sand processed from tunnel slag crushing, with a fineness modulus of 2.68.

[0044] Example

[0045] This embodiment first provides a green, low-carbon, high-performance shotcrete using active regenerated micropowder, the raw materials include the following components by weight: 300-350 parts of cement; 50-80 parts of active regenerated micropowder; 60-120 parts of early-strength mineral admixture, further 80-110 parts; 20-40 parts of rubber powder, further 25-40 parts; 10-20 parts of hydrophobic densifier, further 12-20 parts; 700-800 parts of coarse aggregate, 800-900 parts of fine aggregate; water reducer, the addition amount is 0.8% to 1.2% of the mass of the cementitious material, fluorine-free alkali-free quick-setting agent, the addition amount is 6% to 9% of the mass of the cementitious material; 163-200 parts of water. The cementitious material of this embodiment refers to the sum of cement, active regenerated micropowder and early-strength mineral admixture.

[0046] The active regenerated micropowder is composed of polyisomeric alcohol amine and regenerated micropowder, and the amount of polyisomeric alcohol amine is 0.1% to 0.5% of the mass of the gelling material; the structural formula of the polyisomeric alcohol amine is as follows (Formula 1):

[0047]

[0048] Among them, m=1 or 2, s=0, 1, 2, 3 or 4.

[0049] Furthermore, the recycled concrete powder is obtained by crushing, removing impurities and grinding waste concrete, and the recycled brick powder is obtained by crushing, removing impurities and grinding waste sintered bricks. The recycled concrete powder with the original concrete strength grade of C30 and above is preferably used as the recycled micro-powder in the present invention; the recycled micro-powder must meet the requirements of fineness (45μm square hole sieve residue) ≤45%, particle size ≤75μm, water demand ratio ≤115%, and activity index ≥60%. The activity index of the recycled micro-powder after chemical activation is 70-80%.

[0050] The early strength mineral admixture is a mixture of at least one of fly ash, slag powder, limestone powder and at least one of silica ash, zeolite powder, metakaolin, steel slag powder, phosphorus slag powder and an early strength agent, and the weight ratio of the three is (30-60): (30-40): (10-20) respectively.

[0051] Furthermore, the fly ash is Class F Grade I fly ash, the slag powder is Class S105 slag powder, and the 28d activity index of the limestone powder is ≥70%.

[0052] Furthermore, the silica fume 28d activity index is ≥100%, the zeolite powder is grade I zeolite powder, the steel slag powder is grade I steel slag powder, the phosphorus slag powder is grade L95 phosphorus slag powder, and the metakaolin is ultrafine kaolin calcined at 600°C to 900°C to form high-activity powder particles with a particle size of about 1250 meshes.

[0053] Furthermore, the early strength agent is any one of sodium sulfate, calcium sulfate, magnesium sulfate, sodium thiosulfate, sodium thiocyanate, calcium nitrate, calcium nitrite, and sodium nitrate.

[0054] The rubber powder is the rubber powder of waste tires after surface treatment, and the surface treatment includes any one of water washing method, pre-coating with gelling material method, and chemical solution immersion method, among which the pre-coating with gelling material method or the chemical solution immersion method is preferred.

[0055] The hydrophobic compacting agent is a silicone waterproofing agent or an emulsion waterproofing agent. Type of concrete anti-seepage hydrophobic compound pore plug. It is a concrete admixture with hydrophobic and compacting function. It improves the water repellency of concrete by changing the surface pressure of the capillary pores inside the concrete, and at the same time refines the capillary pore structure to improve the density of concrete, thereby improving the durability of shotcrete in the environment of seepage, sulfate, chloride and other corrosive media.

[0056] The coarse aggregate is 5-10 mm continuously graded natural crushed stone or crushed stone processed by crushing tunnel slag. The coarse aggregate is preferably crushed stone processed by crushing tunnel slag, with a needle and flake particle content of ≤5.0%, a mud content of ≤0.5%, and a mud block content of ≤0.2%.

[0057] The fine aggregate is any one of natural river sand, machine-made sand or a mixture of natural river sand and machine-made sand, with a fineness modulus of 2.5 to 3.2. The fine aggregate is preferably machine-made sand processed by crushing tunnel slag, with a fineness modulus of 2.6 to 3.0, and a mud content of ≤2.0%, a mud block content of ≤0.5%, and a stone powder content of ≤5.0%.

[0058] The water reducer is a mixture of a polycarboxylate water reducer and a slump retaining agent, and the polycarboxylate water reducer is at least one of a carboxylate water reducer, a sulfonate water reducer, and a phosphonate water reducer. Further, the polycarboxylate water reducer is a mixture of a sulfonate water reducer and a phosphonate water reducer, and the mass ratio of the sulfonate water reducer to the phosphonate water reducer is 1:(1.5-3), and the phosphonate water reducer is a phosphonate water reducer with an acid-ether ratio of 2.0-2.5 and a molecular weight of 15,000-20,000.

[0059] The present application also provides a method for preparing green, low-carbon, high-performance shotcrete using active regenerated micropowder, comprising the following steps:

[0060] S1. Dry mix cement, active regeneration powder, early strength mineral admixture, rubber powder, coarse aggregate and fine aggregate;

[0061] S2, add water, water reducing agent, and hydrophobic densifier in sequence and stir evenly to obtain a concrete mixture. The concrete mixture obtained in step S2 must meet the requirements of slump of 180-220 mm, slump loss of 1h ≤ 30 mm, expansion of 450-550 mm, and collapse time of 3-6 s.

[0062] The present application provides a construction process for green, low-carbon, high-performance shotcrete using active regenerated micropowder. In the construction project, the concrete spraying distance is controlled at 0.8 to 1.2 m, the spraying angle is controlled at 80° to 90°, the spraying wind pressure is controlled at 0.8 to 0.9 MPa, and the single-layer spraying thickness is not more than 5 cm.

[0063] The following is an explanation through specific examples.

[0064] Examples 1-4

[0065] In Examples 1-4, the regenerated micropowder is the regenerated micropowder obtained by crushing, removing impurities and grinding the waste concrete (strength grade C50) obtained by dismantling a pedestrian overpass on a highway in Anqing City; the original regenerated micropowder has a fineness of 12.2%, a particle size of 62 μm, a water demand ratio of 105%, and an activity index of 63.6%.

[0066] The water reducer is a polycarboxylate water reducer produced by Jiangsu Subot New Materials Co., Ltd., which consists of water reducing component 1# -10%, water reducing component 2# -30%, unsaturated ester of collapse-preserving component -20%, the rest is water, solid content is 25%, and water reduction rate is 32%.

[0067] Example 1

[0068] A method for preparing green, low-carbon, high-performance shotcrete using active regenerated micropowder, the specific steps are as follows:

[0069] S1. Dry-mix 350kg of cement, 60kg of active regenerated micropowder, 90kg of early-strength mineral admixture, 25kg of modified rubber powder, 700kg of coarse aggregate and 850kg of fine aggregate; wherein the active regenerated micropowder is composed of polyisocyanate alcohol amine and regenerated micropowder, and the amount of polyisocyanate alcohol amine is 0.2% of the mass of the cementitious material; in the structural formula of polyisocyanate alcohol amine, m is 1 and s is 1.

[0070] S2, add 200kg of water, 4kg of water reducing agent, and 12kg of hydrophobic densifier in sequence and mix evenly to obtain a concrete mixture. The slump, expansion, and collapse time of the mixture are measured to be 200mm, 485mm, and 3.4s.

[0071] S3. The concrete mixture is transported to the construction site, and the slump loss is measured to be 18mm. It is then loaded into a wet spraying machine, mixed with 40kg of atomized quick-setting agent at the nozzle and sprayed at high speed onto the surrounding rock surface to form green, low-carbon, high-performance sprayed concrete. After the state stabilizes, it is sprayed into a mold placed in advance, and the performance of the test block is tested according to the prescribed test method.

[0072] Example 2

[0073] A method for preparing green, low-carbon, high-performance shotcrete using active regenerated micropowder, the specific steps are as follows:

[0074] S1. Dry-mix 300kg of cement, 80kg of active regenerated micropowder, 110kg of early-strength mineral admixture, 32kg of modified rubber powder, 760kg of coarse aggregate and 830kg of fine aggregate; wherein the active regenerated micropowder is composed of polyisocyanate alcohol amine and regenerated micropowder, and the amount of polyisocyanate alcohol amine is 0.4% of the mass of the cementitious material; in the structural formula of polyisocyanate alcohol amine, m is 1 and s is 1.

[0075] S2, add 186.2kg of water, 4.9kg of water reducing agent, and 18kg of hydrophobic densifier in sequence and mix well to obtain a concrete mixture. The slump of the mixture measured out of the machine is 210mm, the expansion is 505mm, and the collapse time is 4.2s;

[0076] S3. Transport the concrete mixture to the construction site, measure the slump loss to be 10mm, then load it into the wet spraying machine, mix it with 34.3kg of atomized quick-setting agent at the nozzle and spray it at high speed onto the surrounding rock surface to form green, low-carbon, high-performance sprayed concrete. After the state stabilizes, spray it into a mold placed in advance, and test the performance of the test block according to the prescribed test method.

[0077] Example 3

[0078] A method for preparing green, low-carbon, high-performance shotcrete using active regenerated micropowder, the specific steps are as follows:

[0079] S1. Dry-mix 320kg of cement, 75kg of active regenerated micropowder, 100kg of early-strength mineral admixture, 36kg of modified rubber powder, 800kg of coarse aggregate and 800kg of fine aggregate; wherein the active regenerated micropowder is composed of polyisocyanate alcohol amine and regenerated micropowder, and the amount of polyisocyanate alcohol amine is 0.5% of the mass of the cementitious material; in the structural formula of polyisocyanate alcohol amine, m is 1 and s is 1.

[0080] S2, add 178.2kg of water, 5.5kg of water reducing agent, and 15kg of hydrophobic densifier in sequence and mix well to obtain a concrete mixture. The slump of the mixture measured out of the machine is 190mm, the expansion is 475mm, and the collapse time is 5.1s;

[0081] S3. The concrete mixture is transported to the construction site, and the slump loss is measured to be 22mm. It is then loaded into a wet spraying machine, mixed with 45kg of atomized quick-setting agent at the nozzle and sprayed at high speed onto the surrounding rock surface to form green, low-carbon, high-performance sprayed concrete. After the state stabilizes, it is sprayed into a mold placed in advance, and the performance of the test block is tested according to the prescribed test method.

[0082] Example 4

[0083] A method for preparing green, low-carbon, high-performance shotcrete using active regenerated micropowder, the specific steps are as follows:

[0084] S1. Dry-mix 350kg of cement, 50kg of active regenerated micropowder, 80kg of early-strength mineral admixture, 40kg of modified rubber powder, 780kg of coarse aggregate and 900kg of fine aggregate; wherein the active regenerated micropowder is composed of polyisocyanate alcohol amine and regenerated micropowder, and the amount of polyisocyanate alcohol amine is 0.1% of the mass of the cementitious material; in the structural formula of polyisocyanate alcohol amine, m is 1 and s is 1.

[0085] S2, add 163.2kg of water, 5.8kg of water reducing agent, and 20kg of hydrophobic densifier in sequence and mix well to obtain a concrete mixture. The slump of the mixture measured out of the machine is 184mm, the expansion is 460mm, and the collapse time is 5.6s;

[0086] S3. The concrete mixture is transported to the construction site, and the slump loss is measured to be 23mm. It is then loaded into a wet spraying machine, mixed with 28.8kg of atomized quick-setting agent at the nozzle and sprayed at high speed onto the surrounding rock surface to form green, low-carbon, high-performance sprayed concrete. After the state stabilizes, it is sprayed into a mold placed in advance, and the performance of the test block is tested according to the prescribed test method.

[0087] Example 5

[0088] The difference from Example 1 is that, in the polyisomeric alcohol amine of (Formula 1), m is 1 and s is 0.

[0089] Example 6

[0090] The difference from Example 1 is that, in the polyisomeric alcohol amine of (Formula 1), m is 1 and s is 2.

[0091] Example 7

[0092] The difference from Example 1 is that, in the polyisomeric alcohol amine of (Formula 1), m is 2 and s is 3.

[0093] Example 8

[0094] The difference from Example 1 is that, in the polyisomeric alcohol amine of (Formula 1), m is 2 and s is 4.

[0095] Comparative Example

[0096] Comparative Example 1

[0097] Comparative Example 1 is to replace the active regenerated micropowder in Example 1 with ordinary regenerated micropowder of the same mass, without adding polyisocyanate amine, and the remaining raw material compositions, proportions, and test methods are the same as those in Example 1.

[0098] Comparative Example 2

[0099] Comparative Example 2 is a method in which the early-strength mineral admixture in Example 2 is replaced with an equal-mass common mineral admixture, namely, 100% fly ash. The remaining raw material compositions, proportions, and test methods are the same as those in Example 2.

[0100] Comparative Example 3

[0101] Comparative Example 3 is that the modified rubber powder in Example 3 is replaced with cement of equal mass, and the remaining raw material compositions, proportions, and test methods are the same as those in Example 3.

[0102] Comparative Example 4

[0103] Comparative Example 4 is a method in which the hydrophobic densifier in Example 4 is replaced with water of equal mass, and the remaining raw material compositions, proportions, and test methods are the same as those in Example 4.

[0104] Comparative Example 5

[0105] Comparative Example 5 is to replace the water reducer in Example 1 with an equal mass of ordinary polycarboxylate water reducer (10% by mass fraction of water reducing mother liquid 5% mass fraction of collapse-preserving component and 3% by mass of sodium gluconate, a retarding component. The remaining raw material compositions, proportions and test methods are the same as those in Example 1.

[0106] Comparative Example 6

[0107] Comparative Example 6 is to replace the accelerator in Example 1 with an alkali-free fluorine-containing accelerator of equal mass. The remaining raw material compositions, proportions, and test methods are the same as those in Example 1.

[0108] Comparative Example 7

[0109] The difference from Example 1 is that the stimulator is diethanolamine.

[0110] Comparative Example 8

[0111] The difference from Example 1 is that the stimulator is sodium sulfate.

[0112] Comparative Example 9

[0113] The difference from Example 1 is that in the polyisomeric alcohol amine of Formula 1, m is 0 and s is 1.

[0114] Comparative Example 10

[0115] The difference from Example 1 is that the amount of the polyisomeric alcohol amine used is 1.0% of the mass of the gelling material.

[0116] Performance Testing

[0117] The preparation method and performance test method of the shotcrete specimen in this application are as follows:

[0118] The preparation and rebound rate test methods of shotcrete specimens refer to JGJ / T 372-2016 "Technical Specifications for the Application of Shotcrete", adopt the wet spraying molding process, and use the Gengli Machinery GSP-D dry and wet dual-purpose concrete spraying machine. The specific steps are as follows:

[0119] (1) Weigh the above raw materials in sequence and mix them evenly in a forced mixer. The slump out of the machine must meet the requirements of 180-220 mm, expansion 450-550 mm, and collapse time 3-6 s.

[0120] (2) The mixture is transported to the tunnel construction site by a concrete transport truck and tested for slump loss, which must not exceed 30 mm. It is then loaded into a wet spraying machine, mixed with an accelerator and sprayed onto the surrounding rock. After the state is stable, it is sprayed into a pre-placed large plate test mold with dimensions of 450 mm × 450 mm × 120 mm and a truncated cone test mold with dimensions of 175 mm (upper opening) × 150 mm (height) × 185 mm (lower opening).

[0121] (3) After the spraying is completed, the test mold is placed in the tunnel and cured under the same conditions for 18 hours before demolding. The 1d compressive strength specimen is cut into 100mm×100mm×100mm cubic specimens 2 hours before the age. The long-age specimen is cut or drilled according to the specified size after standard curing for 7 days.

[0122] The compressive strength at 1d, 7d, 28d and 56d was tested in accordance with GB / T 50081-2019 "Standard for Test Methods of Physical and Mechanical Properties of Concrete"; the water penetration resistance (water penetration height method), chloride ion penetration resistance (electric flux method), sulfate erosion resistance, frost resistance (quick freezing method) and shrinkage rate (contact method) were tested in accordance with GB / T 50082-2009 "Standard for Test Methods of Long-term Performance and Durability of Ordinary Concrete". The test results are shown in Tables 1 and 2.

[0123] Table 1 Test results of compressive strength and rebound rate of shotcrete

[0124]

[0125]

[0126] Table 2 Shotcrete durability test results

[0127]

[0128]

[0129] By comparing the performance of Examples 1-4 and Comparative Examples 1-4, it is found that the concrete of the embodiments of the present application not only effectively reduces the amount of cement used and reduces carbon emissions, but also has good early strength, late strength and durability. At the same time, the concrete of the present application is also suitable for the construction process of shotcrete, which can increase the density of shotcrete, improve workability, mechanical strength and durability, etc.

[0130] Analysis of the performance of Examples 5-8 revealed that different polyisomeric alcohol amines have a certain influence on the performance of concrete, but the polyisomeric alcohol amines of the present application can meet the high performance requirements of shotcrete. In addition, for the activator of the present application, Comparative Examples 7 and 8 use diethanolamine and sodium sulfate as activators, respectively, Comparative Example 9 uses polyisomeric alcohol amines of other structures, and Comparative Example 10 adds too much polyisomeric alcohol amine. The concrete not only has a reduced compressive strength, but also an increased rebound rate, which cannot meet the high performance requirements of shotcrete.

[0131] It can be seen from Comparative Examples 1-6 that Comparative Example 1 replaces the active regenerated micropowder in Example 1 with an equal mass of ordinary regenerated micropowder, and does not add polyisomeric alcohol amines, and the performance in all aspects is greatly reduced; Comparative Example 2 replaces the early strength mineral admixture in Example 2 with an equal mass of ordinary mineral admixture, and the compressive strength is reduced. Comparative Example 3 replaces the modified rubber powder in Example 3 with an equal mass of cement, and the compressive strength is reduced compared with Example 3, and the rebound rate is greatly increased; Comparative Example 4 replaces the hydrophobic densifier in Example 4 with an equal mass of water. In addition to the reduction in compressive strength, its rebound rate is greatly increased, and the durability is greatly reduced, which is not suitable for shotcrete; Comparative Example 5 replaces the water reducer in Example 1 with an equal mass of ordinary polycarboxylic acid water reducer. Not only does the compressive strength of the concrete decrease significantly, but the rebound rate is also too high. Comparative Example 6 replaces the accelerator in Example 1 with an equal mass of fluorine-containing alkali-free accelerator The compressive strength decreased significantly, and the impermeability decreased significantly. This shows that in the concrete system of the present application, each component is indispensable, while reducing the cement dosage of shotcrete, it also has good compressive strength, durability and other properties, and is suitable for the high performance requirements of shotcrete.

[0132] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A green, low-carbon, high-performance shotcrete using active regenerated micropowder, characterized in that: The raw materials include the following components by weight: 300-350 parts of cement, 50-80 parts of active regeneration micro powder, 60-120 parts of early strength mineral admixture, 20-40 parts of rubber powder, 10-20 parts of hydrophobic densifier, 700-800 parts of coarse aggregate, 800-900 parts of fine aggregate; water reducer, the addition amount is 0.8% to 1.2% of the mass of cementitious material; fluorine-free and alkali-free quick setting agent, the addition amount is 6% to 9% of the mass of cementitious material; The active regenerated micropowder is composed of polyisomeric alcohol amine and regenerated micropowder, and the amount of the polyisomeric alcohol amine is 0.1% to 0.5% of the mass of the gelling material; the structural formula of the polyisomeric alcohol amine is as follows (Formula 1): Wherein, m=1 or 2, s=0, 1, 2, 3 or 4; The early strength mineral admixture is a mixture of at least one of fly ash, slag powder, limestone powder and at least one of silica ash, zeolite powder, metakaolin, steel slag powder, phosphorus slag powder and an early strength agent, and the weight ratio of the three is (30-60): (30-40): (10-20) respectively.

2. The green, low-carbon, high-performance shotcrete using active regenerated micropowder according to claim 1, characterized in that: The regenerated micro powder must meet the requirements of fineness (45 μm square hole sieve residue) ≤ 45%, particle size ≤ 75 μm, water requirement ratio ≤ 115%, and activity index ≥ 60%.

3. The green, low-carbon, high-performance shotcrete using active regenerated micropowder according to claim 1, characterized in that: The fly ash is Class F Grade I fly ash, the slag powder is Class S105 slag powder, and the 28d activity index of the limestone powder is ≥70%.

4. The green, low-carbon, high-performance shotcrete using active regenerated micropowder according to claim 1, characterized in that: The silica fume 28d activity index is ≥100%, the zeolite powder is grade I zeolite powder, the steel slag powder is grade I steel slag powder, the phosphorus slag powder is grade L95 phosphorus slag powder, and the metakaolin is ultrafine kaolin calcined at 600°C to 900°C to form high-activity powder particles with a particle size of about 1250 meshes.

5. The green, low-carbon, high-performance shotcrete using active regenerated micropowder according to claim 1, characterized in that: The early strength agent is any one of sodium sulfate, calcium sulfate, magnesium sulfate, sodium thiosulfate, sodium thiocyanate, calcium nitrate, calcium nitrite, and sodium nitrate.

6. The green, low-carbon, high-performance shotcrete using active regenerated micropowder according to claim 1, characterized in that: The rubber powder is waste tire rubber powder that has been surface treated, and the surface treatment includes any one of a water washing method, a pre-coating gelling material method, and a chemical solution immersion method.

7. The green, low-carbon, high-performance shotcrete using active regenerated micropowder according to claim 1, characterized in that: The hydrophobic compacting agent is a silicone waterproofing agent or an emulsion waterproofing agent.

8. The green, low-carbon, high-performance shotcrete using active regenerated micropowder according to claim 7, characterized in that: The hydrophobic compacting agent is -VI type concrete anti-seepage hydrophobic compound pore plug.

9. The green, low-carbon, high-performance shotcrete using active regenerated micropowder according to claim 1, characterized in that: The coarse aggregate is natural crushed stone with continuous grading of 5 to 10 mm or crushed stone processed by crushing tunnel slag.

10. The green, low-carbon, high-performance shotcrete using active regenerated micropowder according to claim 1, characterized in that: The fine aggregate is any one of natural river sand, machine-made sand or a mixture of natural river sand and machine-made sand, and the fineness modulus is 2.5 to 3.

2.

11. The green, low-carbon, high-performance shotcrete using active regenerated micropowder according to claim 1, characterized in that: The water reducer is a mixture of a polycarboxylate water reducer and a slump retaining agent, and the polycarboxylate water reducer is at least one of a carboxylate water reducer, a sulfonate water reducer, and a phosphonate water reducer.

12. The green, low-carbon, high-performance shotcrete using active regenerated micropowder according to claim 11, characterized in that: The polycarboxylate water reducer is a mixture of a sulfonate water reducer and a phosphonate water reducer, and the mass ratio of the sulfonate water reducer to the phosphonate water reducer is 1:(1.5-3). The phosphonate water reducer has an acid-ether ratio of 2.0-2.5 and a molecular weight of 15,000-20,000.

13. A method for preparing green, low-carbon, high-performance shotcrete using active regenerated micropowder according to any one of claims 1 to 12, characterized in that: The following steps are involved: S1. Dry mix cement, active regeneration powder, early strength mineral admixture, rubber powder, coarse aggregate and fine aggregate; S2. Add water, water reducing agent and hydrophobic densifier in sequence and mix well to obtain a concrete mixture.

14. The construction process of green, low-carbon, high-performance shotcrete using active regenerated micropowder according to claim 13, characterized in that: In the construction project, the concrete spraying distance is controlled at 0.8-1.2m, the spraying angle is controlled at 80°-90°, the spraying wind pressure is controlled at 0.8-0.9MPa, and the single-layer spraying thickness is not greater than 5cm.

Citation Information

Patent Citations

  • A high-strength, low-rebound shotcrete and its construction process

    CN108046712B

  • Sprayed concrete as well as preparation method and application thereof

    CN109437706A

  • An economical and environmentally friendly tunnel shotcrete and construction process

    CN110627446B

  • A shotcrete and its construction method

    CN112047708B

  • Special high-strength composite water reducing agent for shotcrete and production process thereof

    CN109293275A

Cited By

  • High-performance sprayed concrete and preparation method thereof

    CN120136493A

  • A high-performance shotcrete and its preparation method

    CN120136493B

  • Low-temperature adaptive early-strength accelerator for sprayed concrete as well as preparation method and application of low-temperature adaptive early-strength accelerator

    CN121377602A